The Bad Guys in the others?! - Blabey, Aaron ([New York, New York] : Scholastic Inc., 2022)
OK. A lot of the stuff we said on the back of the last book was NOT TRUE. We now admit that The Bad Guys is WEIRD. We also admit that it features ALL the weird stuff we said it didn't. PLUS there's now a whole bunch of even weirder stuff involving an over-sharing bat, a really scary new character who lives in the woods, and a strangely confident little guy with a mullet. So, uh, don't relax, maybe FREAK OUT a little and have your MIND BLOWN by the BAD GUYS!
3.5
3-6
Keywords: Animals -- Comic books, strips, etc; Animals -- Juvenile fiction; Heroes -- Comic books, strips, etc; Heroes -- Juvenile fiction; Humorous stories; Animals -- Fiction; Heroes -- Fiction; Humorous comics; Graphic novels; Comics (Graphic works)